miR-214 modulates cisplatin sensitivity of osteosarcoma cells through regulation of anaerobic glycolysis - Song, Y-D.; Li, D-D.; Guan, Y.; Wang, Y-L.; Zheng, J. (Cellular and Molecular Biology, 2017)
Osteosarcoma is the most frequent primary bone tumor originating from adolescents and young adults. Despite improvements in the chemo- or radio- therapy of osteosarcoma patients, survival rate has not increased and drug resistance becomes a major factor that limits the effectiveness. Therefore, investigation of new treatment modalities is urgently required to optimize therapeutic options. Our previous study described an oncogenic role of miR-214 through promotion of osteosarcoma cells proliferation. In this study, we report miR-214 contributes to cisplatin resistance in osteosarcoma cells. Overexpression of miR-214 decreased the cisplatin sensitivity. By establishing an osteosarcoma cisplatin resistant cell line, we find miR-214 is significantly upregulated in cisplatin resistant cells. Moreover, we show miR-214 promotes anaerobic glycolysis rates of osteosarcoma cells but suppresses mitochondrial oxidative phosphorylation. Consistently, cisplatin resistant cells exhibit upregulated glycolysis but decreased mitochondrial oxidative phosphorylation, a phenotype called "Warburg effect”. Finally, we demonstrate inhibition of glycolysis by either glycolysis inhibitor or miR-214 inhibition significantly re-sensitizes cisplatin resistant osteosarcoma cells. In summary, this study illustrates a miRNA-involved chemosensitivity of osteosarcoma and will contribute to the developments of therapeutic agents for the anti-chemoresistance treatments.